2012
DOI: 10.1007/s12088-012-0251-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Diversity of Yeasts in the Mangrove Ecosystems in Fujian, Guangdong and Hainan Provinces of China

Abstract: Mangrove wetland is a unique ecosystem and has rich bioresources. In this article, the roots, stems, branches, leaves, barks, fruits, and flowers from 12 species of the mangrove plants and six species of the accompanying mangrove plants, seawater and sediments in mangrove ecosystems in China were used as sources for isolation of yeasts. A total of 269 yeasts strains were obtained from the samples. The results of routine identification and phylogenetic analysis showed that they belonged to 22 genera and 45 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…isolated from diseased marine animals (Wang et al, 2009a, b). In our previous study (Chi et al, 2012b;Liu et al, 2009;Zhang et al, 2012), it was found that some strains of A. pullulans did not produce any melanin during their cell growth. They may be identified to be different new varieties of A. pullulans.…”
Section: #2mentioning
confidence: 95%
See 1 more Smart Citation
“…isolated from diseased marine animals (Wang et al, 2009a, b). In our previous study (Chi et al, 2012b;Liu et al, 2009;Zhang et al, 2012), it was found that some strains of A. pullulans did not produce any melanin during their cell growth. They may be identified to be different new varieties of A. pullulans.…”
Section: #2mentioning
confidence: 95%
“…are ubiquitous species found mainly in soil, including Antarctic soils, water, the phylloplane, wood, and many other plant materials, rocks, monuments and limestone (Urz'| et al, 1999). In recent years, they also have been found to be widely distributed in hypersaline habitats, coastal water, deep sea, marine sediments of Antarctica and mangrove systems (Chi et al, 2012b;Gunde-Cimerman et al, 2000;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Melanin had an obvious effect on an extremely halotolerant and black yeast Hortaea werneckii survival to the oxidative stress caused by H 2 O 2 (Kejzar et al 2013). Like seawater, the mangrove ecosystems are also characterized by high concentration of NaCl and other salts (Chi et al 2012). Therefore, A. melanogenum P5 strain had higher tolerance to high concentration of NaCl than the non-melanized yeast cells of the yeast strain XJ5-1.…”
Section: Tolerance To High Nacl Concentrationmentioning
confidence: 99%
“…Amplification of its Internal Transcribed Spacer (ITS1 region) and D1/D2 domain of the 26S rRNA gene from the genomic DNA by PCR was performed according to the methods described by Chi et al (2012). The common primers for amplification of the ITS and the 26S rDNA in the yeast were used, the forward primers for the ITS and the 26S rDNA were IT-5 and XJS5, respectively, and the reverse primers for the ITS and the 26S rDNA were IT-6 and XJS3, respectively ( Table 1).…”
Section: Routine and Molecular Identifications Of The Yeast Strain Xj5-1mentioning
confidence: 99%
See 1 more Smart Citation